THE BREAKAWAY REGIONS IN EUROPE (CATALONIA REGION AS A MODEL) - Ass. Prof. Dr. Vian Ahmed Muhammad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The European continent suffers from the presence of some separatist tendencies,the effect of racial and ethnic variables driving the crystallization of separatist conflicts, led to the success of some of them in establishing sovereign states, while the other failed to achieve this. The research focused on the importance of matching geographical, cultural and political criteria in the success of separatist tendencies.It also focused on the role of policies imposed by the mother country in curbing or exacerbating the separatist trend, during the level of fairness in the distribution of wealth between the regions, what were the rights and duties of those persecuted and battered minorities. Therefore, the research focused on presenting a model for separatist movements in the European continent, whose countries are democracies and regular states, clarifying where the problem lies for those minorities that want to secede.